2011
DOI: 10.1177/0047287511426341
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Smartphones in Mediating the Touristic Experience

Abstract: Mobile phones have evolved to be smart computers (smartphones) supporting a wide range of information services that can be accessed anytime and from (almost) anywhere. With the increasing number of users and greater incursion into people's life, smartphones have the potential to significantly influence the touristic experience. This study explores the mediation mechanisms of smartphones by examining stories provided by travelers related to their use of smartphones (and associated applications) for traveling pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
354
0
35

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 626 publications
(431 citation statements)
references
References 48 publications
9
354
0
35
Order By: Relevance
“…While tourism traditionally lagged behind in discussing co-creation in research and applying its principles in practice, it is evident that co-creation has gained increasing recognition. Particularly in the field of technology, scholarship has highlighted the potential of ICTs to mediate experiences and enable opportunities for co-creation in a number of different ways (Tussyadiah & Fesenmaier, 2009;Wang, Park, & Fesenmaier, 2012). Tourists use social media and networking applications as central tools to connect and share experiences (Kim & Tussyadiah, 2013;Neuhofer et al, 2012), engage and co-create experiences with an array of actors, e.g.…”
Section: An Era Of Connectednessmentioning
confidence: 99%
See 1 more Smart Citation
“…While tourism traditionally lagged behind in discussing co-creation in research and applying its principles in practice, it is evident that co-creation has gained increasing recognition. Particularly in the field of technology, scholarship has highlighted the potential of ICTs to mediate experiences and enable opportunities for co-creation in a number of different ways (Tussyadiah & Fesenmaier, 2009;Wang, Park, & Fesenmaier, 2012). Tourists use social media and networking applications as central tools to connect and share experiences (Kim & Tussyadiah, 2013;Neuhofer et al, 2012), engage and co-create experiences with an array of actors, e.g.…”
Section: An Era Of Connectednessmentioning
confidence: 99%
“…companies, at any time (McCabe, Sharples, & Foster, 2012;Sfandla & Björk, 2013;Sigala, 2012b). Mobile technologies are key tools to amplify these practices to gather information (Wang et al, 2012) and support experiences by involving these networks anywhere on the move (Kim & Tussyadiah, 2013).…”
Section: An Era Of Connectednessmentioning
confidence: 99%
“…Thus tourism mobilities research is responding to the call for -better theorization and research, especially to examine the interdependencies between changes in physical movement and in electronic and tablet computers, and social media-expand and modify the traditional contours of tourism (Mascheroni, 2007;White and White, 2007;Paris, 2010Paris, , 2012Germann Molz, 2012;Wang, Park, and Fesenmaier, 2012;Tussyadiah and Fesenmaier, 2008). These new technologies are reconfiguring both time and space (Green, 2002) for their users as they become more ubiquitous parts of daily life.…”
Section: New Technologiesmentioning
confidence: 99%
“…Some researchers have suggested that these advancements allow for tourists to be more creative (Richards, 2011) and spontaneous (Wang, Park, and Fesenmaier, 2012). Positioning Systems (GPS) and a wide range of mobile ‗apps' to locate and provide location specific information for people (Frith, 2012).…”
Section: New Technologiesmentioning
confidence: 99%
“…Para Elisa Martín, directora de tecnología e innovación de IBM España, este proyecto enlaza el mundo físico con la información que lo describe, dos mundos -el físico y el digitalque antes estaban desconectados 6 . Este tipo de apps manifiestan el potencial de aplicaciones creativas de las tecnologías asociadas a la revolución de la movilidad, en especial los smartphones como soporte de experiencias durante el viaje (Wang, Park, & Fesenmaier, 2012). Todo ello constituye una etapa diferente denominada e-tourism (Buhalis, 2003), que no solo utilizaba tecnologías previas diferentes, sino que estaba principalmente centrada en el antes (planificación y reserva) y el después del viaje.…”
Section: Actas Del Seminario Internacional Destinos Turísticos Inteliunclassified